(untitled) (Fiep Bulletin - online, 2013)
This article is a literature review that sought review studies on the quality of life of patients with chronic venous ulcers, for both search was conducted in databases indexed (LILACS, MEDLINE, COCHRANE, HIGWIRE PRESS, PUB MED, ISI WEB SCIENCE, SCIELO), found 41 articles and analyzed 31. They all deal with the repercussions of venous ulcers in patients’ lives by contributing to the poor quality of life of these. Covering issues such as conduct therapy, psychological factors and instruments that measure the quality of life of chronic venous ulcers. Leading us to conclude that physical factors, psychological and socio-economic resulting from venous ulcers may adversely affect the quality of life of patients and therefore indipensable to health care professionals the knowledge of all these factors to an adequate assistance.